TINJAUAN YURIDIS PENYELESAIAN PERKARA KEPAILITAN ANTARA PT. MIMI KIDS GARMINDO DENGAN BANK NUSANTARA PARAHYANGAN - Alifya, Santri; Ismi, Hayatul; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Bankruptcy is a general confiscation of all the assets of a Bankrupt debtor whose management and settlement is carried out by a curator under the supervision of the Supervising Judge as regulated in the Bankruptcy Act. Provisions on simple proof as stipulated in the Bankruptcy Act are very concise and are not supported by a series of provisions and other explanations in the rule that contain clear characteristics of simple evidences especially about what must be proven in simple evidencesThis type of research can be classified in normative legal research, namely legal research conducted by researching library materials. This study examines the subject matter in accordance with the scope and identification of the problem through a statute approach carried out by examining the laws and regulations that relate to the legal issue under study. In this study the authors conducted a study of the principles of law by utilizing descriptive methods. Data collection techniques used in the Normative Legal Research are library research methods (library research) which uses the library as a means of collecting data, by studying books as reference material related to the problems to be studied.The conclusion that can be obtained from the results of the study is the Settlement of bankruptcy cases between PT. Mimi Kids Garmindo with Bank Nusantara Parahyangan based on Decision Number 146 / Pdt.Sus-PKPU / 2017 / PN.Niaga. Jkt. PST still has not provided legal certainty. the requirement to file for bankruptcy is the lawmakers' negligence in formulating Article 2 paragraph (1), in the absence of a “unable to pay” requirement, the creditor can easily submit a request for bankruptcy statements without having to prove that the company is unable or insolvent. Proof of regulation in the case of PKPU in Act Number 37 of 2004 Concerning Bankruptcy and Delaying Obligations of Debt Payment is not as simple as intended in Article 8 paragraph (4) of the Bankruptcy Law. It is still often found in debtor bankrupt trials that have been proven to have more than two creditors and one of the debts has fallen into disrepair, but cannot be bankrupt on the pretext that debtors' debts are complicated debts and are not the authority of the Commercial Court because the principal the dispute must be proven in the District Court.Keywords: Juridical Review, Settlement, Bankruptcy Case,